Evaluasi Pembuatan Prototype Package Tray Biokomposit Serat Tebu- Polypropylene untuk Kebutuhan Interior Mobil - Patrik Permana Putra Wijaya; Juliana Anggono (Institute of Research and Community Outreach, Petra Christian University, 2020)
Natural fibers used in the fabrication of biocomposite product can support the need of the industries for lightweight yet strong material. Sugarcane bagasse is one of the available natural fibers in Indonesia. There have been some research done on these bagasse fibers as reinforcement materials for plastics and their incorporation to the matrix has improved its strength. This research aimed to evaluate the fabrication of a car package tray prototype. The composition and the bagasse were prepared in accordance with the previous research in which the bagasse were alkali treated using NaOH solution of 8 wt% for one hour at room temperature. The hotpressed prototype was evaluated by its physical outlook and the mechanical property of its preform. The flexural test shows a low flexural strength of the prototype (7.4 MPa) compared to the required strength of the current material (woodboard) used by the industry (35.58 MPa). The evaluation shows the clustering of bagasse fibers, uneven distribution of sugarcane/PP in the structure and low adhesion at the interfacial region between bagasse fibers and PP.